Combustion flame spray of CoNiCrAlY & YSZ coatings - Fanicchia, F.; Axinte, D.; Kell, J.; McIntyre, R.; Brewster, G.; Norton, A.D. (Elsevier, 2017)
The properties of CoNiCrAlY and ∼7–8%YSZ layers, used as thermal barrier coatings (TBC) to protect hot gas paths of power generation and aerospace gas turbines, that have been deposited through the Combustion Flame Spray (CFS) process, are assessed and compared to coatings of the same materials deposited through Atmospheric Plasma Spray (APS). Fuel-to-oxygen equivalence ratio, combustion and carrier gases flows, torch standoff distance and powder feed rate values have been varied during the CFS tests in order to assess their effect on microstructural characteristics, i.e. thickness, total porosity, oxide level and microhardness. Results show that, in CFS-deposited coatings, although a higher content of oxide strings and porosity is observed compared to APS, also comparable phase transformations and a higher thermal cyclic lifetime can be achieved with an appropriate tuning of the deposition parameters. Thus, the study demonstrates the excellent capability of the CFS process in depositing thermal barrier coating systems, providing a viable alternative deposition technology for this class of materials at significant hardware simplicity. As the CFS setup has a simple design, this research stimulates a miniaturisation concept of the combustion flame spray torch for allowing its deployment into highly restricted workspaces.